Spatially indirect transitions in electric field tunable quantum dot diodes - Rai, Ashish K.; Gordon, Simon; Ludwig, Arne; Wieck, Andreas D.; Zrenner, Artur; Reuter, Dirk (physica status solidi (b))

Decentralized Controller Reconﬁguration Strategies for Hybrid System Dynamics based on Product-Intelligence - Bertelsmeier, Fabian; Trächtler, Ansgar (20th IEEE International Conference on Emerging Technologies and Factory Automation)

Produkt- und lastabhängiges dezentrales Motormanagement für die Fördertechnik: Anforderungen, Design und Applikation - Bertelsmeier, Fabian; Vathauer, Marc; Henke, Christian; Vathauer, Karl-Ernst; Trächtler, Ansgar (Automation 2015)

Modelling the Constitutive Behaviour of Martensite and Austenite in Shape Memory Alloys Using Closed-Form Analytical Continuous Equations - Pai, Arathi; Niendorf, Thomas; Krooß, Philipp; Koke, Isabel; Trächtler, Ansgar; Schaper, Mirko (7th ECCOMAS Thematic Conference on Smart Structures and Materials - SMART)

Intelligente Biegeverfahren - Damerow, Ulf-Hendrik; Borsig, Michael; Tabakajew, Dmitri; Schaermann, Waldemar; Hesse, Marc; Homberg, Werner; Trächtler, Ansgar; Jungeblut, Thorsten (wt Werkstattstechnik online)

Online-Rekonﬁguration hybrider Regelkreise in Abhängigkeit variierender Produkteigenschaften - Bertelsmeier, Fabian; Engelmeier, Tobias; Trächtler, Ansgar (Tagungsband Mechatronik 2015)

Modellbasierte Mehrzieloptimierung zur Integration von Hausgeräten in SmartGrids - Michael, Jan; Hillebrand, Michael; Dumitrescu, Roman; Henke, Christian; Trächtler, Ansgar (VDI Mechatronik 2015 Tagungsband)

Real-Time Compatible Phenomenological Modelling of the Austenitic Phase in Shape Memory Alloys as an Example for Modelling of Materials with Repeatable Non-Linear Characteristics - Pai, Arathi; Trächtler, Ansgar; Schaper, Mirko (IFAC 1st Conference on Modelling, Identification and Control of Nonlinear Systems - MICNON)

Towards a sustainable and economic selection of part candidates for Additive Manufacturing - Lindemann, C.; Jahnke, U.; Reiher, T.; Koch, R. (Rapid Prototyping Journal)
Purpose – This paper aims to present a methodology to help end-users to find appropriate part candidates for the use of the additive manufacturing (AM) technology. These shall be capable of bringing AM into their businesses. The concept furthermore includes approaches for redesigning current available parts and helps to estimate the economic implications of the use of the technology. Design/methodology/approach – The approach starts to discuss general economic aspects for the successful use of AM. While describing the introduction of new technologies into existing businesses, the importance of an appropriate part selection for AM is pointed out. A methodology for a part selection process is presented, and the different criteria are developed. An approach for a redesign of the selected parts, including the gathering of requirements, is given based on different sample parts. A variation of criteria to include measures for product piracy is highlighted. Findings – The methodology has proven applicability in several research and industry projects in aerospace applications. Independent part selections from experts analyzed within a project of the European Space Agency had a 90 per cent overlap with the results. It allows companies with only basic AM knowledge to start a part screening for applicable AM candidates in their own company with a reasonable effort. Originality/value – The methodology for the redesign process helps to identify the main functions of the products targeted and the relevant environment, so one can benefit from the various advantages that AM has to offer. The selection methodology helps to ask the right questions and to reduce the effort.

Developement of an economic decision support for the application of Additive Manufacturing in aerospace - Deppe, G.; Lindemann, C.; Koch, R. (26th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing offers a high potential in aerospace industry due to its freedom of design and the ability to manufacture complex and lightweight parts. The low number of units, high quality standards and fast response time are special challenges that have to be met especially in the Maintenance, Repair and Overhaul sector. Thus, companies have to decide at which point it is economic to apply Additive Manufacturing. However, companies lack experience on this new technology. This is why a tool is required that takes into account the above mentioned crucial points and supports the decision process. The paper analyzes aviation’s characteristics with regard to Additive Manufacturing. The structure of current MRO repair workflows is investigated to identify a feasible application for Additive Manufacturing. Additionally the supply chain will be examined to indicate the benefit which the technology can generate in this highly demanding field. The findings are integrated into a methodology that supports the decision whether to apply Additive Manufacturing on the basis of costs, time and quality.

Protection measures against product piracy and application by the use of AM - Jahnke, U.; Büsching, J.; Reiher, T.; Koch, R. (26th Annual International Solid Freeform Fabrication Symposium)
Presently the implications Additive Manufacturing (AM) on intellectual properties are discussed in public. Here AM is often mentioned as a driver for product piracy as it allows to produce and to copy objects with any geometries. Imitators need a lot of information to copy an object accurately. As reverse engineering has been identified as the most important information source for product imitators, AM can also help to reduce the threat of product piracy when correctly applied in the product development. Due to the layer wise production process that allows the manufacturing of very complex shapes and geometries, the reverse-engineering process can be complicated by far. By this, quite contrary to the public opinion, AM can increase the needed effort of imitators and strongly reduce the economic efficiency of product piracy. This paper will show different protection measures and a methodological approach of how to apply these measures to a product. Beside the protective effect some measures allow a traceability of parts over the product’s lifecycle and thus support the quality management of AM processes and additively produced parts.

FE-Optimization and data handling for Additive Manufacturing of structural parts - Reiher, T.; Koch, R. (26th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing (AM) offers high potential due to its freedom of design for structural parts. Especially in combination with FE-based topology optimization an optimal use of material and thus significant weight reductions can be expected. However, the application of AM is hampered by different additional manufacturing processes along the entire production chain and data handling induced restrictions.Disadvantages emerge from a lack of adjustment of the entire design process for AM. First the optimization algorithms are not targeted to the opportunities and restrictions of AM –represented by design rules – like the design of support structures. Secondly, the CAD software is not adjusted to AM in particular. Creating freeform shaped surfaces based on the optimization results is significantly less convenient than building defined blocks or turning parts following the needs of conventional machining. The indispensable subsequent interpretation of optimization results regarding the design rules and the possibilities of CAD-tools counteracts optimal results. This paper considers different approaches for a Topology Optimization (TO)-shape regaining on different sample parts including telecommunication satellite parts. An innovative design methodology is presented getting crucial for creating high quality designs.

Sustainable Part Selection for the Use of Additive Manufacturing in Companies Focussing on Prevention of Product Piracy - Jahnke, U.; Lindemann, C. (Inside 3D Printing Conference and Expo)

Exploring the cost and lifetime benefits of a topology optimized aerospace part applying additive manufacturing - Deppe, G.; Reiher, T.; Koch, R. (International Conference Production Engineering and Management 2015)
The aerospace sector is characterized by long product life cycles and a need for lightweight design. Additive manufacturing is a technology that produces parts layer by layer and thus enables the manufacturing of any complex parts at nearly no extra costs. A topology optimization enhances the part’s performance for their special purpose. The results are often complex bionic structures that cannot be produced with conventional manufacturing technologies. The paper analyzes how the high potential of this technology can be applied to aerospace parts. A topology optimization will be conducted for an aircraft part explaining the crucial points and a life cycle analysis examines the achieved sustainable improvements for the aircraft’s life cycle.

Guidelines for a sustainable and economic selection of part candidates for space applications using additive manufacturing - Lindemann, C.; Reiher, T.; Koch, R. (Paris Space Week)

Analysis and Optimization of the Dimensional Accuracy for FDM Parts manufactured with ABS-M30 - Knoop, F.; Schöppner, Volker (ASPE Spring Topical Meeting)

Mechanical and Thermal Properties of FDM Parts manufactured with Polyamide 12 - Knoop, F.; Schöppner, Volker (26th Annual International Solid Freeform Fabrication Symposium)
Fused Deposition Modeling (FDM) is an Additive Manufacturing (AM) technology which is used for prototypes, single-part production and also small batch productions. For use as a final product, it is important that the parts have good mechanical properties, high dimensional accuracy and smooth surfaces. The knowledge of the mechanical properties is very important for the design engineer when it comes to the component design. End-use products out of the FDM process have to resist applied forces. In this paper, investigations were conducted with the polymer Polyamide 12 (FDM Nylon 12) from Stratasys Inc. This polymer can be processed with three different tip sizes resulting in different layer thicknesses from 178 µm to 330 µm. Thus, the mechanical properties were determined for these layer thicknesses and for different orientations on the build platform. In addition to the mechanical properties the thermal properties (e.g. with a DSC analysis) are also investigated.

Integrating Human-Centered and Model-Driven Methods in Agile UI Development - Fischer, Holger Gerhard; Yigitbas, Enes; Sauer, Stefan (Proceedings of 15th IFIP TC.13 International Conference on Human-Computer Interaction (INTERACT))

Qualitätsdimensionen für interaktive Systeme - Stand der Arbeiten UPA AK Qualitätsstandards - Fischer, Holger Gerhard; Polkehn, Knut; Geis, Thomas; Kluge, Oliver; Behrenbruch, Kay; Riedemann, Catharina (Mensch und Computer 2015 - Usability Professionals)

Mensch und Computer 2015 - Usability Professionals. Tagungsband